2017
DOI: 10.12691/ajnr-5-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deferred Versus Early Umbilical Cord Clamping on Maternal and Neonatal Outcomes

Abstract: Background: Recent protocol proposed by the World Health Organization to manage the third stage of labour replaced the early cord clamping by deferred cord clamping to induce numerous neonatal benefits. But this practice is still resisted in most of the Arab countries. The aim of this study was to evaluate the effectiveness of deferred versus early umbilical cord clamping on maternal and neonatal outcomes. Methods: A quasi experimental research design was utilized. The study was conducted at labour unit in Dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 35 publications
6
13
0
Order By: Relevance
“…Despite increasing evidence, delayed cord clamping is still not practiced in most Arab countries [3,13,21,22]. Relatively few studies have investigated the effects of early versus delayed cord clamping on maternal and neonatal outcomes in Arab countries, with the exception of studies conducted in Egypt and Saudi Arabia [3,9,13]. In the current study, the authors found that delayed cord clamping had a positive impact on newborns and mothers compared to those receiving early cord clamping.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Despite increasing evidence, delayed cord clamping is still not practiced in most Arab countries [3,13,21,22]. Relatively few studies have investigated the effects of early versus delayed cord clamping on maternal and neonatal outcomes in Arab countries, with the exception of studies conducted in Egypt and Saudi Arabia [3,9,13]. In the current study, the authors found that delayed cord clamping had a positive impact on newborns and mothers compared to those receiving early cord clamping.…”
Section: Discussionmentioning
confidence: 61%
“…Recent recommendations by WHO [4] included delayed cord clamping to manage the third stage of labor and promote various maternal and neonatal benefits. Despite increasing evidence, delayed cord clamping is still not practiced in most Arab countries [3,13,21,22]. Relatively few studies have investigated the effects of early versus delayed cord clamping on maternal and neonatal outcomes in Arab countries, with the exception of studies conducted in Egypt and Saudi Arabia [3,9,13].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations